MALAY CULTURAL VALUES IN MALAYSIAN ANIMATION: A MULTIMODAL ANALYSIS - Nur Afifah Atirah binti Saperi, - (Universiti Malaysia Sarawak, 2022)
Animation has evolved into an aesthetic object that plays a significant role to transmit messages and information, with its distinctive advantages and great impacts on people’s daily lives. In this new era, Malaysian animation is en route towards becoming a global phenomenon in the animation industry as it is capable to compete against influential animation worldwide. It is notable that Malaysian animation has won audiences hearts, with its unique representation of local values, especially Malay cultural values. As many researchers have been conducted Malay cultural values in animation based on its types, non-material culture or intangible objects is not prevalently used to describe Malay cultural values. To emphasize, no full attention is given too on how Malay cultural values are portrayed with related visuals that are simultaneously exhibited with dialogues in the animation. Therefore, this study seeks to examine the portrayal of Malay cultural values in Malaysian animation using the multimodal analysis approach, by focusing on the types of Malay cultural values, how these types of Malay cultural values are portrayed in Malaysian animation, including the extent to which Malaysian animation functions as a ‘culture broker’ based on the Malay cultural values that it portrays. This study employs Katan theory (cultural items classification), Lim Kim Hui theory (Molecurization of Budi), Awang, Maros and Ibrahim theory (other Malay values) for qualitative content analysis, as well as quantitative analysis, including Kress and van Leeuwen metafunctional framework for multimodal analysis to analyze 40 texts and 255 visuals from Upin & Ipin: The Lone Gibbon Kris film. The findings show that there are many types of Malay cultural values in terms of material and non-material cultures, and the visuals are portrayed concurrently with the dialogues in the animation in certain ways. In addition, the results have contributed to the evaluation of animation potentiality to function as a culture broker. Hence, it is concluded that the animation which can be a culture broker, can be addressed by future researchers to find out further whether the latter can function in actuality or vice versa.